Understanding strategies for overcoming peripherality: A Polish experience of transition - Wójcik, Marcin; Dmochowska-Dudek, Karolina; Jeziorska-Biel, Pamela; Tobiasz-Lis, Paulina (Bulletin of Geography. Socio-economic Series, 2018)
This article addresses the problematic county of Wieruszów-a peripheral area of Poland, constituting a classic case of historical development away from urban agglomerations, additionally burdened by the stigma of a former near-border location, and later (including today) functioning at the fringe of an administrative district. The area in question exemplifies structural transformations associated with changes in patterns of accessibility to large urban agglomerations following the coming into operation of a key expressway. The work detailed here has sought to analyse the aforementioned area's position vis-a-vis accessibility, as set against the background of factors justifying the description of "inner periphery". An essential element in accounting for any strategy for overcoming this peripherality takes the form of the results of in-depth interviews carried out by the authors. Joint consideration of the two perspectives mentioned, i.e. the structural (showing the position of a given area in relation to its proximate (regional) and ultimate (national) environments), and the social (i.e. the expert assessment), ultimately allowed for an assessment of opportunities and threats as far as the overcoming of peripherality in its geographic and social dimensions is concerned.